Self-trapping and excited state absorption in fluorene homo-polymer and copolymers with benzothiadiazole and tri-phenylamine. Issue 31 (21st July 2016) - Denis, Jean-Christophe; Ruseckas, Arvydas; Hedley, Gordon J.; Matheson, Andrew B.; Paterson, Martin J.; Turnbull, Graham A.; Samuel, Ifor D. W.; Galbraith, Ian
Abstract : Excited state absorption (ESA) is studied using time-dependent density functional theory and compared with experiments performed in dilute solutions. Abstract : Excited state absorption (ESA) is studied using time-dependent density functional theory and compared with experiments performed in dilute solutions. The molecules investigated are a fluorene pentamer, polyfluorene F8, the alternating F8 copolymer with benzothiadiazole F8BT, and two blue-emitting random copolymers F8PFB and F8TFB. Calculated and measured spectra show qualitatively comparable results. The ESA cross-section of co-polymers at its maximum is about three times lower than that of F8. The ESA spectra are found to change little upon structural relaxation of the excited state, or change in the order of sub-units in a co-polymer, for all studied molecules. In all these molecules, the strongest ESA transition is found to arise from the same electronic process, exhibiting a reversal of the charge parity. In addition, F8PFB and F8TFB are found to possess almost identical electronic behaviour.